(untitled) (Orinoquia, 2020)
An activated sludge processes (ASP) plug flow reactor (PFR) was developed in this research and used for determining optimal cell residence time (CRT) for treating high leachate loads and estimating the system’s kinetic behaviour as a basis for scaling projections and this type of reactor design at full-scale. The RFP was designed, built and put into operation in the laboratory (50L capacity) involving continuous operation conditions with sludge recirculation; leached substrate from the city of Cúcuta’s El Guayabal landfill was used. Four 5-day CRTs (ranging from 5 to 20 days) were used as control parameters. Variables were evaluated regarding pH, temperature, dissolved oxygen and mixed liquor volatile suspended solids (MLVSS). Regarding removal efficiency control and monitoring, chemical oxygen demand (COD) was chosen as a parameter for measuring organic matter degradation since COD (unlike biochemical oxygen demand (BOD5)) can be calculated in a shorter time. The RFP biological system became stabilised in a 20- to 25-day operating period, having greater than 92% average removal for 15- and 20-day CRTs, whilst lower CRTs reported lower than 86% average removal. A 15-day TRC gave an average 0.26 kgDQO/kgSSV.d optimal load factor (F/M). The representative kinetic constants obtained in this research for a laboratory-scale PFR system for the removal of carbonaceous organic matter in leachates were KS = 836mg COD / l, k = 4.8123 d1, Y = 0.089 mg SSVLM / mg COD and kd = 0.018 d-1, adjusted by regression using Lawrence and McCarty’s mathematical model (having 0.97 correlation between the experimental data and the model). Such model should have broad application in the field of ASP-type PFRs.